(3GdJfHjg Ydi GdGNJdGa hGdJaGhJ hGdJfGbV aj cJGH GdCOhjI GdeaQOI ef GdbGfhfs - (3CaVd GdOjf YeQ Hf Ydj Hf ZjdGf GdHdNis; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3bGd GdTjN ahLOJ ef GdCNJdGa hGdJaGhJ hGdJfGbV eG jOd Ydi Cf CLd eG ajg efbhd ef cJH ef ZjQ QhjI ai fbdg hGYJfG HGdJMbjb ajg s
(3BNQgG (B:s
(3HGdbjGS Zdi eNWQaGJ GHf SjfG ai GdYdhe GdMbjbjI GdJi fGbV ajgG GdMb hNGda HgG GdESdGe Je HYhf Gddg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(1538) s
Keywords: (3GdWHs